Β-blockers: Their new life from hypertension to cancer and migraine. (January 2020) - Fumagalli, Carlo; Maurizi, Niccolò; Marchionni, Niccolò; Fornasari, Diego
Graphical abstract: Abstract: The pharmacological class of β-blockers includes a plea of molecules with largely different pharmacokinetic and pharmacodynamic characteristics with a protective effect that may span far beyond the cardiovascular system. Although all these compounds share the pharmacological blockade of the adrenergic receptors, each of them is characterized by specific pharmacological properties, including selectivity of action depending on the adrenergic receptors subtypes, intrinsic sympathomimetic activity (ISA), lipid solubility, pharmacokinetic profile, and also other ancillary properties that impact their clinical effect. Their use in the treatment of hypertension has been extensively debated and at the moment a class indication is not present. However, in specific niche of patients, such as in those young individuals in which hypertension is mainly driven by a sympathetic hyperactivation, strong evidence pose β-Blockers as a highly reasonable ﬁrst-line treatment. Lipophilic β-blockers, specifically propranolol and metoprolol, can cross the Blood Brain Barrier and have a Class A indication for the prophylactic treatment of migraine attacks. Moreover, since β-adrenergic receptors affect the proliferative process of both cancer and immune cells, their blockade has been associated with metastasis reduction in several epithelial and solid organ tumors posing β-Blockers as a new attractive, inexpensive and relatively safe therapeutic strategy in patients with several types of cancer. However, further dedicated prospective, randomized, placebo-controlled studies are needed to determine the real efficacy of these compounds.